2022
DOI: 10.1108/ijtc-05-2022-0108
|View full text |Cite
|
Sign up to set email alerts
|

Conflicting discursive representations of overtourism in Lisbon in the Portuguese digital press

Abstract: Purpose This study aims to explore the ways in which Portuguese online news reports and opinion studies have framed the discussion about overtourism in Lisbon and its impacts on the city and its inhabitants. Design/methodology/approach Drawing on critical discourse analysis applied to media texts, this paper discusses the discursive representations of overtourism by focusing on how an emerging new discourse which constructs tourism as problematic began to challenge the established discourse – in which touris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Ribeiro & Torkington (2023) examined how Portuguese online news reports address overtourism in Lisbon and the impact it has on the city and its residents. Using critical discourse analysis, they found that the media often uses legitimating strategies to highlight the benefits of tourism growth while also using de-legitimating strategies to minimize overtourism issues.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ribeiro & Torkington (2023) examined how Portuguese online news reports address overtourism in Lisbon and the impact it has on the city and its residents. Using critical discourse analysis, they found that the media often uses legitimating strategies to highlight the benefits of tourism growth while also using de-legitimating strategies to minimize overtourism issues.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a direct result of over-tourism raised by academics, these studies point two issues with accommodation and re-urbanization of traditional neighborhoods to lure tourists (Daly et al, 2021). These issues include rising housing costs, displacing locals, and harming the environment (Ribeiro & Torkington, 2022). Furthermore, the increase in immigration is also directly related to the problem of adequate housing for the Lisbon population (Da Cunha et al, 2023), in addition to significantly affecting the Portuguese culture.…”
Section: Lisbon As a Digital Nomad's Destinationmentioning
confidence: 99%
“…The issue of over-tourism has emerged as a significant concern due to the disproportionate mobility of tourist access juxtaposed with the carrying capacity of destination sites, eliciting a myriad of comments and sentiments from both local communities and travelers seeking to derive meaning from their tourism experiences [9]. The rapid growth of tourism has led to overcrowding, environmental degradation, and socio-cultural disruption in popular destinations worldwide, underscoring the urgency of addressing this imbalance [10]. As destinations struggle to cope with the influx of visitors, tensions arise between the aspirations of tourists and the preservation of local heritage and livelihoods [11].…”
Section: Introductionmentioning
confidence: 99%